Histopathological Evaluationof Appendectomy Specimens in a Tertiary Care Hospital - Noreen, Fozia; Ghazal, Lubna; Ambreen, Salma; Malik, Tariq Masood; Iqbal, Anjum; Tehseen, Tahira (Pakistan Armed Forces Medical Journal, 2022)
Objective: To find out the histopathological findings in appendectomy specimens, negative appendectomy rate (NAR) and the association of gender and age groups which underwent negative appendectomies in our set up.Study Design: Cross sectional study.Place and Duration of Study: POF Hospital, Wah Cantt, from Jan to Aug 2017.Methodology: The records of 1050 patients were assessed for the relevant clinical history, age, gender and date of their presentation in hospital. The appendectomy specimens were classified as positive specimens which contained fecoliths, worms, granulomatous inflammation, foreign body reaction, mucocele, or appendiceal tumors. All the data were entered and analyzed in SPSS-21.Results: Among the 1050 patients with suspicion of acute appendicitis, 458 (43.6%) were cases of acute appendicitis followed by acute suppurative appendicitis 100 (9.5%) and fecolith 79 (7.5%) in appendiceal lumen. The negative appendectomy rate was calculated as 248 (23.6%). A significant association of normal appendices was found with female gender (p=0.002) and young age group (p=0.02).Conclusion: Acute appendicitis was the most frequent histopathological finding in our study. The negative appendectomy rate was significantly associated with the females of young age.